Modification of bacterial cells for in vivo remotely guided systems - Rybkin, Iaroslav; Pinyaev, Sergey; Sindeeva, Olga; German, Sergey; Koblar, Maja; Pyataev, Nikolay; Čeh, Miran; Gorin, Dmitry; Sukhorukov, Gleb; Lapanje, Aleš (Frontiers in Bioengineering and Biotechnology, 2023)
It was shown recently that bacterial strains, which can act specifically against malignant cells, can be used efficiently in cancer therapy. Many appropriate bacterial strains are either pathogenic or invasive and there is a substantial shortage of methods with which to monitor in vivo the distribution of bacteria used in this way. Here, it is proposed to use a Layer-by-Layer (LbL) approach that can encapsulate individual bacterial cells with fluorescently labeled polyelectrolytes (PE) and magnetite nanoparticles (NP). The NP enable remote direction in vivo to the site in question and the labeled shells in the far-red emission spectra allow non-invasive monitoring of the distribution of bacteria in the body. The magnetic entrapment of the modified bacteria causes the local concentration of the bacteria to increase by a factor of at least 5. The PEs create a strong barrier, and it has been shown in in vitro experiments that the division time of bacterial cells coated in this way can be regulated, resulting in control of their invasion into tissues. That animals used in the study survived and did not suffer septic shock, which can be attributed to a PE capsules that prevent release of endotoxins from bacterial cells.